2015
DOI: 10.1038/nnano.2015.75
|View full text |Cite
|
Sign up to set email alerts
|

Single quantum emitters in monolayer semiconductors

Abstract: Abstract:Single quantum emitters (SQEs) are at the heart of quantum optics 1 We assign this fine structure to two excitonic eigen-modes whose degeneracy is lifted by a large ~0.71 meV coupling, likely due to the electron-hole exchange interaction in presence of anisotropy 8 . Magneto-optical measurements also reveal an exciton g-factor of ~8.7, several times larger than that of delocalized valley excitons 9-12 . In addition to their fundamental importance, establishing new SQEs in 2D quantum materials could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

67
955
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 886 publications
(1,034 citation statements)
references
References 34 publications
67
955
12
Order By: Relevance
“…their energies are nearly overlapped with the L broadband seen at low pressure, as represented by DL1 and DL2 marked in exciton decay time of a few ns of a discrete line is in agreement with the typical value for the quantum emitters in 2D materials. 3,10 Instead, the reported decay time of the broad L excitons is shorter, from ten picoseconds 16 to hundreds picoseconds. 17 This means that the lifetime of discrete lines is about one or two order longer than the lifetime of the broad L band emission.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…their energies are nearly overlapped with the L broadband seen at low pressure, as represented by DL1 and DL2 marked in exciton decay time of a few ns of a discrete line is in agreement with the typical value for the quantum emitters in 2D materials. 3,10 Instead, the reported decay time of the broad L excitons is shorter, from ten picoseconds 16 to hundreds picoseconds. 17 This means that the lifetime of discrete lines is about one or two order longer than the lifetime of the broad L band emission.…”
mentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8][9] Local strain gradients which occur at the edges are considered to modulate the electronic states of the localized excitons, 2, 9-11 resulting in spatially and spectrally isolated single photon emission. This means that strain engineering is an effective approach to obtain spatially and spectrally isolated quantum emitters in two-dimensional (2D) semiconductors.…”
mentioning
confidence: 99%
“…Our scheme for valley pseudospin manipulation should also extend to the recently discovered quantum-confined states of excitons in TMDC layers [29][30][31][32][33] . For these localized excitonic states, the valley pseudospin degree of freedom is expected to be well preserved 34 , but their lifetimes are far longer than for the free excitons examined in this work.…”
mentioning
confidence: 97%
“…[6][7][8][9] In particular, defect-derived excitonic states have recently received much attention for their applications in single-photon emitters. To date, several groups have reported that atomic-layer TMDCs show photoluminescence (PL) from optically active defects at low temperature (4 ∼ 90 K).…”
mentioning
confidence: 99%
“…To date, several groups have reported that atomic-layer TMDCs show photoluminescence (PL) from optically active defects at low temperature (4 ∼ 90 K). [6][7][8][9][10][11] Such a two-dimensional (2D) single-quantum emission has practical advantages in efficient photon extraction and high integration capability. However, the details of such defect sites are still unclear, and PL can generally be observed only at low temperature.…”
mentioning
confidence: 99%